Evaluation of Intraocular Pressure Changes Following Trabeculectomy with Mitomycin-C (MMC): A One-Year Follow-Up Study at Undaan Eye Hospital, Indonesia - Kesuma, Raudhatuzzahra; Nuradianti, Lydia; Soraya, Debby; Audina, Rizna (Universitas Airlangga, 2025)
Introduction: Trabeculectomy with mitomycin-C (MMC) is a widely used surgical intervention for the management of glaucoma. This study aimed to evaluate changes in intraocular pressure (IOP) before and after surgery, using statistical analyses of pre-operative and post-operative IOP measurements. Purpose: To determine the effectiveness of MMC in trabeculectomy and its role in enhancing surgical success. Methods: This retrospective observational study analyzed the medical records of 65 eyes from 52 glaucoma patients who underwent trabeculectomy with 2% MMC at Undaan Eye Hospital, Surabaya, Indonesia, between 2022 and 2023. Post-operative IOP was assessed at one, three, six, and twelve months. Statistical analyses were performed to identify patterns of IOP change over time. Results: A Kruskal-Wallis test, followed by Dunn's post hoc analysis (p < 0.001), revealed significant differences in IOP between the pre-operative and post-operative periods (p < 0.05). However, no significant differences were found among post-operative follow-up intervals (p > 0.05). Correlation analysis of IOP categories (< 20 mmHg vs. ≥ 20 mmHg) across observation points showed a negative correlation (r = -0.491, p < 0.001), indicating a tendency for IOP reduction over time. Regression analysis estimated that IOP decreased by approximately 1.141 mmHg per month. Conclusions: Significant reductions in IOP were observed post-operatively, with a sustained downward trend compared to pre-operative values. These findings provide valuable insights into the long-term effectiveness of trabeculectomy with MMC, emphasizing factors that optimize surgical outcomes for glaucoma management.